High intake of orange juice and cola differently affects metabolic risk in healthy subjects. Issue 2 (April 2019) - Büsing, Franziska; Hägele, Franziska A.; Nas, Alessa; Döbert, Laura-Verena; Fricker, Alena; Dörner, Elisabeth; Podlesny, Daniel; Aschoff, Julian; Pöhnl, Tobias; Schweiggert, Ralf; Fricke, W. Florian; Carle, Reinhold; et al.
Summary: Background: Higher consumption of sugar-containing beverages has been associated with an elevated risk of type 2 diabetes and gout. Whether this equally applies to cola with an unhealthy image and orange juice (OJ) having a healthy image remains unknown. Methods: In order to investigate whether OJ and cola differently affect metabolic risk 26 healthy adults (24.7 ± 3.2 y; BMI 23.2 ± 3.3 kg/m 2 ) participated in a 2 × 2-wk intervention and consumed either OJ or caffeine-free cola (20% Ereq as sugar from beverages) in-between 3 meals/d at ad libitum energy intake. Glycemic control, uric acid metabolism and gut microbiota were assessed as outcome parameters. Results: Fecal microbiota, body weight, basal and OGTT-derived insulin sensitivity remained unchanged in both intervention periods. Levels of uric acid were normal at baseline and did not change with 2-wk cola consumption (−0.03 ± 0.67 mg/dL; p > 0.05), whereas they decreased with OJ intervention (−0.43 ± 0.56 mg/dL; p < 0.01) due to increased uric acid excretion (+130.2 ± 130.0 mg/d; p < 0.001). Compared to OJ, consumption of cola led to a higher daylong glycemia (ΔiAUC: 36.9 ± 83.2; p < 0.05), an increase in glucose variability (ΔMAGE-Index: 0.29 ± 0.44; p < 0.05), and a lower 24 h-insulin secretion (ΔC-peptide excretion: −31.76 ± 38.61 μg/d; p < 0.001), which may be explained by a decrease in serum potassium levels (−0.11 ± 0.24 mmol/L; p < 0.05). Conclusion: Despite its sugar content, regular consumption of large amounts of OJ do not increase the risk of gout but may even contribute to lower uric acid levels. The etiology of impaired insulin secretion with cola consumption needs to be further investigated.